EMPOWERED WOMEN REPRESENTED IN RUPI KAUR’S 'MILK AND HONEY' - Normala Putri Adzkiya; Ririn Kurnia Trisnawati; Mia Fitria Agustina (UIN Raden Mas Said Surakarta, 2022)
This paper is the result of the analysis on Rupi Kaur’s poems compiled in her book entitled Milk and Honey. It focuses on how Kaur portrays women from their breaking to healing stages until finally they become strong and empowered figures. This study employed a qualitative-descriptive method for analyzing the poems. By her poems, Kaur speaks her thoughts about women’s representation in society. She also criticizes the patriarchal ideology that places women as the servant for men’s pleasure. Her works illustrate problems that oppress women such as sexual objectification, mental trauma, and family with patriarchal culture. Throughout the book, Kaur also reveals the journey of women from being hurt to be finally healed and become empowered.